1992
DOI: 10.1055/s-2006-961378
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacological Investigations ofAllium ursinumandAllium sativum

Abstract: Extracts of wild garlic (Allium ursinum) and garlic (A. sativum) with defined chemical compositions were investigated for their in vitro inhibitory potential on 5-lipoxygenase (LO), cyclooxygenase (CO), thrombocyte aggregation (TA), and angiotensin I-converting enzyme (ACE). The inhibition rates as IC50 values of both extracts for 5-LO, CO, and TA showed a good correlation with the %-content of the major S-containing compounds (thiosulfinates and ajoenes) of the various extracts. In the 5-LO and CO test the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 5 publications
2
61
1
2
Order By: Relevance
“…Researchers have postulated that antihypertensive action of garlic is due to its prostaglandin like effects, which decreases peripheral vascular resistance [19]. It is shown that gamma-glutamylcysteine compounds in garlic inhibits angiotensin-converting enzyme in vitro which might be involved in blood pressure lowering effect of garlic [37]. Garlic modulates the production and function of both endothelium derived relaxing and constricting factors.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have postulated that antihypertensive action of garlic is due to its prostaglandin like effects, which decreases peripheral vascular resistance [19]. It is shown that gamma-glutamylcysteine compounds in garlic inhibits angiotensin-converting enzyme in vitro which might be involved in blood pressure lowering effect of garlic [37]. Garlic modulates the production and function of both endothelium derived relaxing and constricting factors.…”
Section: Discussionmentioning
confidence: 99%
“…Allium sativum (Liliaceae) Garlic: Although results obtained from clinical studies have been conflicting (Banerjee & Maulik, 2002;Tanamai et al, 2004;Turner et al, 2004), the results from in vitro (preclinical) studies and epidemiologic studies indicate that garlic may be beneficial against cardiovascular disease (CVD) (Rahman & Lowe, 2006). Garlic and its derivatives have been reported to significantly decrease the diastolic BP (DBP) in humans (McMahon & Vargas, 1993), decrease both the circulating ang II levels and the systolic BP (SBP), while increasing the nitric oxide (NO) system activity in hypertensive rats (Mohamadi et al, 2000;Preuss et al, 2001), increase NO production in isolated pulmonary arteries of rats (Kim-Park & Ku, 2000), reduce the increases in ACE activity in serum and various tissues during the development of HTN in the two-kidney-one-clip (2K1C) hypertensive rats (Sharifi et al, 2003), dilate blood vessels (Zahid Ashraf et al, 2005), inhibit angiotensin converting enzyme (ACE) (Sendl et al, 1992), possess anti-oxidative properties (Dillon et al, 2003); increase fibrinolysis , inhibit blood coagulation, inhibit platelet aggregation and thrombus formation (Rahman & Lowe, 2006), reduce lipid levels in blood (Augusti et al, 2005), possess anti-atherogenic and anti-atherosclerotic effect (Elkayam et al, 2003;Kempaiah & Srinivasan, 2005). Undesirable effects have also been reported with the consumption of large doses of garlic (Yadav & Verma, 2004 has been reported to improve cardiac function, reduce afterload, HTN, tachycardia and arrhythmia in both clinical and pharmacological studies (Walker et al, 2006).…”
Section: Plants With Cardiovascular Effectsmentioning
confidence: 99%
“…Diverse compounds suppressing 5-LO product synthesis Sulfur-containing molecules, e. g., certain cepaenes 114, ajoenes 112 and the thiosulfinate allicin 113 (Table 10) from Allium species (i. e., onions and garlic) were found to inhibit 5-LO activity in cell-based assays (IC 50 = 0.5 ± 1, 1.5 and 25 mM, respectively), as well as COX product (TXB 2 and PGE 2 ) synthesis, and histamine release [197], [198]. No or only weak antioxidant properties have been reported for these compounds [199].…”
Section: Alkaloidsmentioning
confidence: 99%
“…Thus, the molecular mechanisms underlying suppression of 5-LO product formation remain to be examined. Extracts of onions and garlic suppress inflammatory and allergic reactions in vivo (in animals as well as in human patients), correlating to the content of S-containing compounds [198], [200]. Recently, constituents (one lignan, one kaurenoate and three bisabolane derivatives) from the root of Leontopodium alpinum (Cass.)…”
Section: Alkaloidsmentioning
confidence: 99%